Enhancing Islamic Moral Development through Effective Boarding School Education Program Management - Muhammad Muklis; Ahmad Sukandar (Jurnal Iman dan Spiritualitas, 2026)
This study aims to analyze the implementation of boarding school education program management in improving Islamic morals at the Al-Qur'an Asy-Syafi'iyah Islamic Boarding School in Garut. This study uses a qualitative approach with field study methods, involving in-depth interviews, participatory observation, and documentation of the boarding school leadership, administrators, ustadz/ustadzah, and students. The results of the study indicate that the management of the boarding school program at this Islamic boarding school runs in an integrated manner through careful planning, professional organization of human resources, consistent implementation of worship habits and moral values, as well as continuous monitoring and evaluation. The synergy between religious and general education, supported by the example of educators and by mandatory programs such as tahsin, tahfidz, and yellow book learning, can create an educational environment conducive to the development of Islamic morals in students. This study also identified several challenges, including the need to strengthen role models among senior students and the importance of collaborating with students' parents. The study concludes that the boarding school management model implemented at the Al-Qur'an Asy-Syafi'iyah Islamic Boarding School is effective in shaping students' Islamic morals and can serve as a reference for the development of Islamic boarding school education in Indonesia.